EFFECT OF COUNSELING OF SALT RESTRICTION IN HYPERTENSIVE PATIENTS - Dr. Javeria Wazir; Dr. Wahaj ul Hassan Khan; Dr. Maryam Hussain; Dr. Jamshed Khan; Dr. Muhammad Yaseen; Dr. Muhammad Mehroon Razzaq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
ABSTRACT Background: Hypertension presents a significant health challenge globally. Dietary modifications, particularly salt restriction, have emerged as crucial, non-pharmacological strategy to manage hypertension. Prior studies have demonstrated the efficacy of salt restriction in reducing blood pressure and cardiovascular risk. Objective: To evaluate the impact of dietary salt restriction counseling on blood pressure management, focusing on individuals with elevated blood pressure, without relying on drugs. Methods: This study was conducted at a tertiary care hospital in Peshawar, Pakistan, targeting individuals aged 30 and above with blood pressure upto140/90. Excluding those with secondary hypertension or complications, the study employed personalized counseling sessions to limit salt intake to 2.5 gm per day (1/2 Teaspoon salt), monitoring participants over 3 and 6 months. The sample size was 288, determined by a 95% confidence level and a 5% margin of error, considering the local prevalence of hypertension. Results: The cohort included 158 males (54.9%) and 130 females (45.1%), with mean weight of 75.5 kg (SD = 15.2) and initial systolic and diastolic blood pressures of 138.7 (SD = 1.5) and 88.4 (SD = 1.1) mmHg, respectively. After 6 months, significant reductions in systolic (127.9 ± 2.0 mmHg) and diastolic (82.9 ± 1.3 mmHg) blood pressures were observed, indicating effective control through dietary salt restriction. Conclusion: Dietary counseling on salt restriction significantly lowers blood pressure in hypertensive patients, offering a non-pharmacological approach to managing hypertension. This strategy can substantially contribute to reduction of cardiovascular risks associated with hypertension.